Literatur Review: Komitmen dan Kepuasan Hidup Perkawinan - Gretty Henofela Huwae (Pusat riset dan Inovasi Nasional, 2025)
This study aims to identify the description of Commitment and Marital life Satisfaction. This study uses the systematic literature review (SLR) method, in order to answer research questions in a structured manner, by referring to the PRISMA 2020 model by reviewing 100 articles with keywords, namely (1) marriage commitment, (2) marriage satisfaction, and (3) commitment and marital life satisfaction. This research used the EndNote X9 application to obtain 5 articles from the Google Scholar database with the help of Harzing Publish or Perish (PoP). The results of this study show that commitment and marital life satisfaction are interrelated in maintaining marital harmony. Commitment, demonstrated through responsibility, support, and long-term orientation, is the foundation of marital stability. Couples with high commitment are better able to deal with challenges such as age difference or long distance thanks to open communication and effective conflict resolution. Factors such as religion, social support and the presence of children also affect satisfaction. Religious values strengthen relationship resilience, while unfulfilled expectations for children can decrease satisfaction.